Changes in Communication Interactions and Perceptions of Aphasia : The Communication Partners Program - Sather, Thomas; Peterson, Ali (My University, 2018)
The purpose of this study was to investigate the changes in communication interactions and perceptions of aphasia among student volunteers in the Communication Partners Program (CPP).
Color poster with text, images, and maps.
Keywords: Speech disorders; Aphasia; Posters